2009
DOI: 10.1074/jbc.m109.021634
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylethanolamine-esterified Eicosanoids in the Mouse

Abstract: In this study, murine peritoneal macrophages from naïve lavage were found to generate four phospholipids that contain 12-hydroxyeicosatetraenoic acid (12-HETE). They comprise three plasmalogen and one diacyl phosphatidylethanolamines (PEs) (16:0p, 18:1p, 18:0p, and 18:0a at sn-1) and are absent in macrophages from 12/15-lipoxygenase (12/15-LOX)-deficient mice. They are generated acutely in response to calcium mobilization, are primarily cell-associated, and are detected on the outside of the plasma membrane. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 25 publications
7
64
0
Order By: Relevance
“…We have also found that LOX isoforms in other innate immune cells including neutrophils and monocytes/macrophages generate analogous lipids on activation, indicating that this is a common theme of likely importance in acute response to injury 33, 129-131 . All these cell types undergo significant changes to the plasma membrane compartment on activation, including shape change, vesiculation, phagocytosis and microvilli generation.…”
Section: Specific Lipid Families In Plateletsmentioning
confidence: 52%
“…We have also found that LOX isoforms in other innate immune cells including neutrophils and monocytes/macrophages generate analogous lipids on activation, indicating that this is a common theme of likely importance in acute response to injury 33, 129-131 . All these cell types undergo significant changes to the plasma membrane compartment on activation, including shape change, vesiculation, phagocytosis and microvilli generation.…”
Section: Specific Lipid Families In Plateletsmentioning
confidence: 52%
“…Although this enzyme can participate in the generation of different classes of eicosanoids, 12/15-LO was recently shown to preferentially oxygenate esterified fatty acids in the form of membrane-bound phosphatidylethanolamine (PE), although the biological consequence of this oxidation process remains largely elusive (Maskrey et al, 2007;Morgan et al, 2009). Analysis of phospholipids in resMF by mass spectrometry confirmed the presence of 12/15-LO-specific PE oxidation products in this macrophage subpopulation.…”
Section: Resident Macrophages Utilize 12/15-lo To Generate Specific Pmentioning
confidence: 58%
“…Even single oxPE species such as PAPE-OH (PAPE reflects around 20%-30% of total PE) are detected in mM concentrations within resMF. Moreover, oxPE is enriched in the outer membrane leaflet in a 12/15-LO-dependent manner (Morgan et al, 2009), which might yield even higher local concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations